Differential Genetic Architecture of Insulin Resistance (HOMA-IR) Based on Obesity Status: Evidence from a Large-Scale GWAS of Koreans - Ja-Eun Choi; Yu-Jin Kwon; Kyung-Won Hong (Current Issues in Molecular Biology)
Insulin resistance (IR) is a key mechanism underlying type 2 diabetes mellitus and is closely associated with obesity. Although numerous genome-wide association studies (GWASs) have identified variants that influence IR-related traits, it remains unclear whether the genetic architecture of IR differs according to obesity status. We conducted a stratified GWAS of the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) in 8906 Korean individuals from the Korean Genome and Epidemiology Study. Participants were categorized into a normal-weight group (Body Mass Index (BMI) ≤ 23 kg/m2) and an overweight or obese group (BMI > 23 kg/m2), and the GWAS was performed separately within each group. No significant genome-wide variants were identified in the normal-weight group; however, seven loci showed suggestive associations. In contrast, in the overweight and obese group, two loci, rs662799 in Apolipoprotein A5 (APOA5) and rs671 in Aldehyde Dehydrogenase 2 (ALDH2), showed genome-wide significance, with seven loci showing suggestive associations. The risk allele of rs662799 was associated with increased HOMA-IR values, with a stronger effect observed in the overweight and obese group. This finding aligns with the known role of APOA5 in triglyceride metabolism, suggesting that a higher BMI may exacerbate its effect on IR. These results highlight obesity-specific genetic susceptibility to IR and the need to consider obesity status in genetic studies of metabolic traits.